Reaksi Paradoksikal pada Kasus Definitif Meningoensefalitis Tuberkulosis - Nagpal, Chand (PERDOSNI, 2023)
PARADOXICAL REACTION IN A DEFINITIVE CASE OF TUBERCULOUS MENINGOENCEPHALITIS ABSTRACT Tuberculous Meningoencephalitis is an infection of the central nervous system (CNS) that is characterized by fever, headaches, nuchal rigidity, focal neurological deficit and altered consciousness. This is a case report illustrating the clinical progress of a 22-year old woman with HIV-negative status diagnosed with definitive tuberculous meningoencephalitis with a paradoxical reaction, which is a clinical syndrome where the patient experiences clinical deterioration after a phase of clinical improvement; syndrome of inappropriate antidiuretic hormone secretion (SIADH) and hydrocephalus, which are two relatively common complications in cases of tuberculous meningitis, which pose as challenges in clinical management of such cases. Ventriculoperitoneal (VP) shunt is an invasive treatment option for the management of hydrocephalus is cases of central nervous system infections that do not respond adequately to pharmacologic therapy. Keywords: meningoencephalitis, paradoxical, SIADH, shunt, tuberculous